Broadening student musicians’ career horizons: The importance of being and becoming a learner in higher education - Bennett, Dawn; López-Íñiguez, Guadalupe (SAGE, 2020)
Research in higher music education acknowledges a persistent divide between performance studies and the realities of musicians’ work. Alongside this is global pressure for curriculum that is more supportive of students’ metacognitive engagement, experiential learning and career preparation. However, scholars assert that the provision of these curricular elements is insufficient unless students recognise their value and engage in them at a deep level; this is because career-long 2 employability in precarious industries such as music is underpinned by strategic, life-long and self-regulated learning. The study reported here featured a scaffolded employability intervention located within the existing curriculum and trialled with seven student musicians at a European institution. The study had three aims: to understand the students’ career-related thinking and confidence; to determine whether such an intervention might be scalable; and to gauge the intervention’s potential efficacy in helping students to become conscious of their learner identity. Results indicate that many student musicians are aware of the need to extend their essential professional capabilities but unaware of how to address these deficits. Participants realised that “learning how to learn” would help them achieve personal and professional goals. The findings suggest that similar in-curricular interventions are achievable at scale. Further, they have the potential to foster a more holistic vision of performance education and practice such that aspiring musicians might graduate as both skilled professionals and agentic learners.